2010
DOI: 10.1111/j.1469-8749.2009.03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spasticity in cerebral palsy: dependence of catch angle on velocity

Abstract: MAS) and 10 typically developing participants (four males, six females; mean age 10y 3mo, SD 2y 7mo, range 7-15y). Spasticity and catch angle were evaluated using joint position, resistance torque, and torque rate at velocities of 90°, 180°, and 270°per second, controlled using real-time audio-visual feedback. Biomechanically, elbow range of motion (ROM), stiffness, and energy loss were determined during slow movement (30°⁄ s) and under controlled terminal torque.RESULTS Compared with typically developing chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 28 publications
4
65
0
Order By: Relevance
“…We also found that the catch angle was linearly dependent on the movement velocity and thus should be determined at a well controlled velocity for consistent results. The linear relation between movement velocity and catch angle was also found in a related study on the upper limb [22]. …”
Section: Discussionsupporting
confidence: 69%
“…We also found that the catch angle was linearly dependent on the movement velocity and thus should be determined at a well controlled velocity for consistent results. The linear relation between movement velocity and catch angle was also found in a related study on the upper limb [22]. …”
Section: Discussionsupporting
confidence: 69%
“…The use of online adaptive classification algorithms for myoelectric pattern recognition is more important for studies involving routine clinical EMG recorded from paretic-spastic muscles. In particular, in studies involving clinical populations (e.g., stroke, spinal cord injury, cerebral palsy) that may have spontaneous motor activity due to spasticity [32][33][34], paretic muscles may present a large amount of long-duration involuntary motor activity, and the involuntary motor activity can lead to relatively high tonic baseline activity [33]. Thus the quality of EMG signals may be degraded by interfering the tonic baseline activity during the recording process in routine clinical environments.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular methods of clinical muscle tone assessment are subjective scales, including the Ashworth Scale (AS), the Modified Ashworth Scale (MAS), the Tardieu Scale (TS), and the Modified Tardieu Scale (MTS) [2,8]. In children with spastic CP, there is a strong correlation between the range of motion (ROM), the velocity of movement, and the position in which the tested muscle reacts to stretching [2,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this test, two joint angles are measured: DROM I, defined as the PROM deficit following a slow velocity stretch, and DROM II, defined as the angle of catch (AOC) after a fast velocity stretch. The difference between DROM II and DROM I indicates the examined muscle group's level of contracture and is called the angle of spasticity (ASO) [2,[10][11][12][13]. The DAROM, again like the MTS, specifies three velocities that can be applied to the Spasticity is a common impairment that interferes with motor function (particularly gait pattern) in children with cerebral palsy (CP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation